A structured autopsy-based audit of 370 firearm fatalities: Contribution to inform policy decisions and the probability of the injured arriving alive at a hospital and receiving definitive care - Iordanis N. Papadopoulos; Nikolaos K. Kanakaris; Nikolaos Danias; Dimitrios Sabanis; George Konstantudakis; Spyridon Christodoulou; Yiannis C. Bassiakos; Christos Leukidis (Accident Analysis & Prevention, 2013)
The objectives of this autopsy-based audit of firearm-related fatalities were to acquire data to inform policy decisions and to assess the probability of the injured arriving alive at a hospital and receiving definitive care. Evaluated variables Demographics; co-morbidities; location and intention of the injury; toxicology; types of firearms; Abbreviated Injury Scale; Injury Severity Score (ISS); transfer means and time; and location of death. Results Of a total of 370 fatalities, 85.7% were male. The median age was 38 (9–95) years. Suicides (47%) and assaults (45.1%) were the most common underlying intentions. The most seriously injured regions were the head (44.5%), thorax (25.7%), abdomen (10.7%), and spine (5.7%). Of the 370 total subjects, 4.9% had an İSS\} < 16 and 59.5% had an İSS\} ≤ 74; both groups were classified as potentially preventable deaths. The majority (84%) died at the scene, and only 9.8% left the emergency department alive for further treatment. Multivariate analyses documented that postmortem İSS\} is an independent factor that predicts the probability of the injured reaching a hospital alive and receiving definitive care. Individuals injured in greater Athens and those most seriously injured in the face, abdomen or spine had significantly greater chances of reaching a hospital alive and receiving definitive care, whereas those injured by a shotgun and the positive toxicology group were significantly less likely to. In conclusion, this study provides data to inform policy decisions, calls for a surveillance network and establishes a baseline for estimating the probability regarding the location of firearm-related deaths.
Keywords: Greece